The same old mistakes in aquaculture: the newly-available striped catfish Pangasianodon hypophthalmus is on its way to putting Brazilian freshwater ecosystems at risk - Garcia, Diego A. Z.; Magalhães, André L. B.; Vitule, Jean R. S.; Casimiro, Armando C. R.; Lima-Junior, Dilermando P.; Cunico, Almir M.; Brito, Marcelo F. G.; Petrere-Junior, Miguel; Agostinho, Ângelo A.; Orsi, Mário L. (Biodiversity and conservation, 2018)
In the state of São Paulo in southeastern Brazil, a dangerous decree allows the culture of hybrids and non-native extralimital fish species in the Paraná and East Atlantic River basins. We recorded the illegal importation and sale of the non-native striped catfish Pangasianodon hypophthalmus in northeastern, central-western, southeastern, and southern areas of the country. This species is already consumed across Brazil and is cultivated for ornamental purposes. Besides escapes from fish farms and ‘fish and pays’, P. hypophthalmus can reach natural environments through aquarium dumping and ornamental ponds, motivated by its large size that reach after being sold at small size. The species has been introduced in many countries, and if established in Brazil, could put native Brazilian biodiversity and ecosystems at risk. Although importing specimens of P. hypophthalmus is prohibited by law, Decree 62.243/2016 in the state of São Paulo creates a new opportunity for invasion. In fact, once a novel fish species is moved to a new continent, it is irrational to supposed that it will stay static just in the area for which it was intended. In general, the fish disperse in the novel area on their own, by escapes from captivity or deliberate and illicit releases by persons or associations. The unwise attitude of Brazilian decision-makers and lay people in their attempt to develop aquaculture with non-native species goes against the objectives of responsible aquaculture based in native species.